Some Investigations on Pulmonary Metastasis of Osteosarcoma - Teshima, R.; Osako, Y.; Maeyama, I.; Ikemoto, K. (Orthopedics & Traumatology, 1974)
The volume doubling time and tumor duration time of pulmonary metastatic nodules in our fifteen cases of osteosarcoma were calculated by Collins' chart and Wollin's formula. Results were as follows. 1. The volume doubling time of osteosclerosing osteosarcoma was generally longer than that of osteolytic osteosarcoma. 2. The chemotherapy for pulmonary metastases prolonged their volume doubling time remarkably. 3. The tumor duration time was ranged from 0.86 to 8.15 years (average 3.32 years). It was suggested that the metastasis of osteosarcoma to the lung might be 2.7 years in average prior to the onset of symptoms of primary lesion. 4. Regarding the growth rate of pulmonary metastases of our cases, the Collins' hypothesis seemed to be considerably acceptable.